SISTEM ISOLASI SEISMIK STRUKTUR GEDUNG RUMAH SAKIT PRATAMA ENREKANG SULAWESI SELATAN - Ade Okvianti Irlan; Muhammad Sofyan (Universitas Trisakti, 2018)
Multi-storey buildings as a place for humans to carry out their activities, both for residential, office buildings, hospitals, business activities, social activities, cultural activities or other special activities. One earthquake resistant building system is a seismic isolation system. Where a storey building is not designed by strengthening its structural resistance to earthquake forces but rather how to reduce earthquake forces acting on the building by adding a structural system that is devoted to absorbing some of the earthquake energy entering the building so that only a small portion (the rest) will borne by the structural components of the building. In this study, we will try to use the base isolator / basic isolation system at the Pratama Hospital building in Enrekang Regency, South Sulawesi. Considering that this Hospital is a fairly strategic public facility in the South Sulawesi region and is included in the category of high-rise buildings that need to be considered when receiving lateral earthquake loads.